Inclusive learning innovation with mobile-based bilingual interactive games for slow learner students - Suastika Yulia Riska; Widya Adhariyanty Rahayu; Abdul Aziz Muslim (University of Merdeka Malang, 2024)
This Community Service Program developed a mobile-based bilingual interactive game called